Implementation, Advantages and Management of ISO 9001 in the Construction Industry - Fazal Ali Shaikh; Samiullah Sohu (Civil Engineering Journal, 2020)
Since 1987, construction companies all over the world welcomed a system for quality management IS0 9001 which was created by the International Organization for standardization. This study aims to recognize the implementation intensity of essential elements of ISO 9001 and the key advantages of ISO 9001 in construction firms after implantation of these elements. Total 51 recognized Pakistani construction companies were considered and studied however the respondent rate remained 59%. Moreover, the analysis of data was done by Statistical Package for the Social Sciences (SPSS) version 27. The most significant advantages and essential elements of ISO 9001 are the results evaluated by the study. Total 34 basic aspects were identified from the previous literature review. The findings of the result showed that the implementation of ISO are very important in construction projects. Identification of current issues and removal of preventable credentials is found most important implementation. Advantages of ISO in the construction industry are Satisfaction of employees, Increment in the ratio of captivation new projects, Decrease in wastage of material and better contacts in global markets respectively. The study will advantage Pakistani construction companies in improving quality work, performance and interest of implementing ISO 9001 will be created in construction firms in regard to groom quality standards.